Co wspólnego mają marka biblioteki i marka osobista bibliotekarza? .......... 73 - Marchel, Paweł (Skąd się biorą czytelnicy?, 2025)
THE INTERSECTION OF THE LIBRARY BRAND AND THE LIBRARIAN PERSONAL BRANDThe article presents the concepts of the library brand and the personal brand of the librarian. Both are closely connected with building the public image of the library. However, the marketing efforts of libraries often focus exclusively on the brand of the institution, while the sphere of the personal brand of librarians is sidetracked. In reality, though, the actual public image of the library is made of both of these. It cannot emerge separately from the activities of the institution, which are shaped mainly by its staff. Therefore, the library management and librarians themselves should try to emphasize the intersection of the library brand and the librarian personal brand. Enhancing both will help to build a strong position of the library.